Sonia: a Biography - Kidwai, Rasheed (New Delhi ; New York, NY : Penguin, 2003)
On the life and times of Sonia Gandhi, b. 1946; leader of the Congress Party and widow of Rajiv Gandhi, b. 1944, former prime minister of India.
A Tragedy in Sriperumbudur (Page-), The Search for A Successor (Page-8), A Long Journey from Orbassano (Page-24), A Tale of Two Bahus (Page-33), The Prime Minister$1 (Bs Wife (Page-43), A Tug of War (Page-52), Education Sonia (Page-78), Sonia Takes over the Congress (Page-103), The Favoured Few (Page-117), Sonia$1 (Bs Faith (Page-129), The New Generation (Page-141), The Rebles (Page-158), The Controversies (Page-172), Sonia the Leader (Page-191), Looking to the Future (Page-205).s
Keywords: Gandhi, Sonia, -- 1946-; Indian National Congress -- Biography; Politicians -- India -- Biography; Prime ministers' spouses -- India -- Biography; India -- Politics and government -- 1947-